POLIMERISASI EMULSI ETIL AKRILAT: PENGARUH KONSENTRASI SURFAKTAN, INISIATOR DAN TEKNIK POLIMERISASI TERHADAP DISTRIBUSI UKURAN PARTIKEL - Helmiyati, Helmiyati; Budianto, Emil; Arinda, Nitri (UI Scholars Hub, 2009)
Emulsion Polymerization of Etyl Acrylate: The Effect of Surfactant, Initiator Concentration and Polymerization Technique on Particle Size Distribution. Emulsion polymerization was conducted using ethyl acrylate monomer. The effect of sodium lauryl sulfate concentration, ammonium persulfate concentration, the various of polymerization techniques and feeding time to the conversion, particle size and its distribution were observed. The purpose of this research is to obtain the optimum condition of ethyl acrylate homopolymer with particle size around 100 nm, to get the particle size distribution monodisperse and to get solid content value of the experiment closed to its theoretical value. The optimum condition then could be applied in shell polymerization of core-shell polymers. The results of the research showed that semicontinuous technique obtained optimum sodium lauryl sulfate concentration at 20 CMC (critical micelle concentration) and ammonium persulfate concentration is 3%. By using batch technique that the biggest particle size is 123 nm with conversion 95.8% and monodisperse. The shorter of feeding time the more monomer of ethyl acrylate being polymerized, it is showed by the higher conversion up to 94.4% and the bigger particle size is 107.9 nm.